Transcutaneous Vagus Nerve Stimulation Does Not Affect Verbal Memory Performance in Healthy Volunteers - Mertens, Ann; Naert, Lien; Miatton, Marijke; Poppa, Tasha; Carrette, Evelien; Gadeyne, Stefanie; Raedt, Robrecht; Boon, Paul; Vonck, Kristl (Frontiers in Psychology, 2020)
1. Abstract Introduction: Vagus nerve stimulation (VNS), using an implant and applied during the consolidation phase of a memory task, improves word recognition in patients with epilepsy. Recent studies with transcutaneous vagus nerve stimulation (tVNS) have shown positive effects on various subdomains of cognitive functioning in healthy volunteers. In this randomized controlled cross-over trial, we investigated the effect of tVNS on a word recognition paradigm in healthy volunteers to further investigate the potential of VNS in the treatment of cognitive disorders. Methods: We included 41 healthy participants aged between 18 and 30 years (‘young age group’) and 24 healthy participants aged between 45 and 80 years (‘older age group’). Each participant conducted a word recognition paradigm during 3 different conditions: ‘true tVNS’, ‘sham and ‘control’ where no stimulation was applied. In each condition, participants were asked to remember highlighted words in 3 test paragraphs. The order of experimental conditions and test paragraphs were randomized across subjects. Between each condition, a wash-out period of 30 minutes was implemented. Accuracy scores were calculated for immediate recall after each test paragraph and for delayed recognition at the end of the paradigm. Results: In this randomized trial, tVNS did not affect the accuracy scores of the immediate recall, nor of the delayed recognition in any of the age groups. The younger group showed significantly higher accuracy scores than the older group. The accuracy scores improved over time and the most recently learned words were better recognized. Participants reported significantly higher pain scores in the true tVNS condition. There was no significant effect of pain reports on accuracy scores. Conclusion: In this study, tVNS did not affect verbal memory performance in a group of young and older healthy volunteers. Our results could not confirm the positive effects of VNS on word recognition with an implant in epilepsy patients. Younger participants performed better on immediate recall and delayed recognition tasks. Pain during stimulation was not a confounding factor in this word recognition paradigm.